2021
DOI: 10.1159/000512491
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Lung and Liver Volume Measurements on Fetal Magnetic Resonance Imaging in Left-Sided Congenital Diaphragmatic Hernia

Abstract: <b><i>Introduction:</i></b> Congenital diaphragmatic hernia (CDH) affects 1 in 3,000 live births and is associated with significant morbidity and mortality. <b><i>Methods:</i></b> A review of fetal magnetic resonance imaging (MRI) examinations was performed for fetuses with left CDH and normal lung controls. Image review and manual tracings were performed by 4 pediatric radiologists; right and left lung volumes in the coronal and axial planes as well as liver vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These disease manifestations are critical outcomes and will be important areas for future study. Finally, inter-reviewer reproducibility was not verified in this study, but has been demonstrated to be moderate-to-good for liver volumes above the diaphragm and good-to-excellent for liver volumes below the diaphragm after standardization ( 23 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These disease manifestations are critical outcomes and will be important areas for future study. Finally, inter-reviewer reproducibility was not verified in this study, but has been demonstrated to be moderate-to-good for liver volumes above the diaphragm and good-to-excellent for liver volumes below the diaphragm after standardization ( 23 ).…”
Section: Discussionmentioning
confidence: 65%
“…All MRI scans were reviewed and reported by 2 independent fetal radiologists with combined 40 years of experience. Using this methodology, intra- and inter-reviewer reproducibility has been demonstrated to be moderate-to-good for liver volumes above the diaphragm and good-to-excellent for liver volumes below the diaphragm after standardization of the technique ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the presented results show high ICCs between segmented lung volumes for repeated acquisitions, which is likely due to the clarity of lung visualization on fetal MRI. Previous studies confirm lung segmentation can be performed reliably, even in severe pulmonary hypoplasia [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the sequence less affected by artifacts can be chosen [ 31 , 32 ]. In addition, this method shows high reproducibility and excellent inter- and intraobserver agreement [ 29 , 32 , 33 ]. In a recent meta-analysis including four studies assessing the role of TFLV in predicting mortality, the absolute lung volume was markedly reduced in patients with poor prognosis, with a significant overall impact on survival [ 12 ].…”
Section: Mri Evaluation and Clinical Implicationsmentioning
confidence: 99%